Konversi Termal kayu ketapang (Terminalia Catappal) Menjadi Bio-Oil Dengan Teknologi Pirolisis Menggunakan Katalis NiMo/NZA - Ari Aditia Sukma; Syaiful Bahri; Aman Aman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Availability of fossil fuels are depleting resulted in higher mining costs and selling prices to the public. In addition, the results of its combustion also releases GHG to the environment. One way to reduce the use of fossil fuels is produce bio-oil through pyrolysis technology. Ketapang rod is a huge potential used as feedstock for bio-oil production because its high cellulose content (41.80%). Synthesis of bio-oil from Ketapang stem begins with the process of size reduction of biomass and natural zeolite to -100+200 mesh size. Then, into the natural zeolite impregnated Ni and Mo to form the bimetallic catalyst NiMo/NZA. The catalyst is then activated through the stages of calcination, oxidation, and reduction. Pyrolysis process is done by varying the weight percentage of catalyst to biomass, ie: 1.5%, 2%, 2.5%, and 3% w/w. In addition, the catalytic pyrolysis process is carried 3% NZA only  and 3% NiMo/NZA were activated by calcination process alone. The highest yield was obtained on the use of catalysts NiMo/NZA perfect activated which amounted to 91.05%. From physics analysis performed on the bio-oil obtained: density of 0.91 g/ml, viscosity 10.839 cSt, acid number 46.954 mg NaOH/g sample, flash point 52oC, and the heating value 42.66 MJ/Kg. The figures are included in the range of physical characteristics of diesel-oil. Five (5) the dominant compound results of chemical analysis by GC-MS of the bio-oil from Ketapang rod by using a catalyst NiMo/NZA 3% by weight are: 3,4,4-trimethyl-2-nonene (10.29%), isobutylene (8.84%), 2,2-dimethyl-butane (8.05%), 3,4,4-trimethyl-2-pentene (5.76%), and 2-methyl-1-heptene (5.26%).  Keywords: Bio-oil, Pyrolysis, and Catalyst NiMo/NZA